Z etymologii polskiej (2): rozgardiasz - Fałowski, Adam (Slavia Occidentalis, 2023)
The article is devoted to the word rozgardiasz (hurly-burly) well-known in general Polish. Its chronology, semantic development, geography, and etymology are presented in a detailed and systematic way. It has been recognised as a Polish-Latin hybrid and a manifestation of the word-forming invention of Jan Mączyński, the author of the Latin-Polish Dictionary from 1564. The word’s forming structure and etymology are not entirely clear. In all probability, three constituent elements can be identified: *roz- + -gard- + -‘as(z), where the initial segment roz- should be interpreted as a prefix with the meaning ‘to break with something, to depart from something, to negate something’, the central segment -gard- can be referred, most likely, to garda [guard], gardość, gardać, gardzić [to despise], hardy [impertinent], hardość [impertinence] etc., with a lexical meaning ‘splendour, superfluity, debauchery, choosiness in eating and drinking’. Most problematic is the interpretation of the final component -‘as(z) which seems to be a nonnative element, probably Latin. This is indicated by the graphic combination -dia-, alien to the Polish language and characteristic of Latin, assimilated on Polish soil as -dyja-, i.e. rozgardyja(s), cf. dialectal rozgardyjo, ozgardyja, ṷozgardyjo, etc. In Latin, -as is the acc. ending of pl. of feminine nouns like discordia, lūxuria, pl. dēliciae, epulae, īnsidiae, cf. Latin discordias prōdūcere (discordia ‘discord, feud’), dēlicias facere (dēliciae pl. ‘sensual pleasures, amusements, amusements, superfluities, delights, enjoyments’), alicuie pulas dare, oculis epulas dare (epulae pl. ‘dishes, dishes; feast, feast’), īnsidias struere (īnsidiae’ intrigues, scheming, deceit’). In the phrase rozgardias(z) stroić, the noun occurs in the accusative. If we assume that this is a copy of the Latin acc. pl. of feminine nouns, then the literal meaning of the conjunction r. stroić should be interpreted as a repeated, recurring activity, i.e. ‘to arrange sensual delights, debauched amusements, games, frolics, luxuries, pleasures; to hold feasts, debauched and sumptuous feasts, with an abundance of exquisite and fanciful food, an excess of the finest liquors and the presence of other carnal pleasures’. This corresponds semantically with the synonymous verbs używać, bonować cited by J. Mączyński. It would also have to be assumed that over time, the acc. pl. of a feminine noun abstracted from the substantive-verbal construction as a masculine noun and began to live its own life. This conception of the genesis of the lexeme in question, although very attractive and internally coherent, is, however, unable to transcend the limits of an academic hypothesis.